1996
DOI: 10.1007/s002340050339
|View full text |Cite
|
Sign up to set email alerts
|

Spiral CT angiography: study of stenoses and calcification at the origin of the vertebral artery

Abstract: The origin of the vertebral artery may be difficult to show on sonography or conventional angiography. Our aim was to evaluate the accuracy of CT angiography (CTA) in detecting arteriosclerotic changes in the first segment (V1) of the vertebral artery. We performed CTA and intra-arterial digital subtraction angiography (DSA) on 24 patients with vertebrobasilar insufficiency. The ostium and the V1 segment were examined. Stenosis was assessed on a three-grade scale, and calcification and the degree of kinking we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 8 publications
3
25
0
1
Order By: Relevance
“…This was done for pragmatic reasons, most stroke patients do not routinely undergo DSA (i.e., because of complication risks). In addition, previous studies show that CTA is adequately capable of detecting vertebral artery stenosis (Farres et al, 1996;Khan et al, 2009). Third, the cause of posterior circulation stroke or TIA might be thrombo-embolic instead of hemodynamic.…”
Section: Discussionmentioning
confidence: 96%
“…This was done for pragmatic reasons, most stroke patients do not routinely undergo DSA (i.e., because of complication risks). In addition, previous studies show that CTA is adequately capable of detecting vertebral artery stenosis (Farres et al, 1996;Khan et al, 2009). Third, the cause of posterior circulation stroke or TIA might be thrombo-embolic instead of hemodynamic.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies reported 94% sensitivity and 88% specificity for multi-detector CT angiography in VA stenoses ≥ 50%. Calcified stenoses in the VA origin can be found by CTA even more easily than by DSA (18). In an investigation, Puchner et al emphasized the high quality and feasibility of multi-detector CTA for diagnosis of vertebral stenoses; however, the correlation value between CTA and DUS was moderate (kappa 0.56).…”
Section: Discussionmentioning
confidence: 99%
“…They used continuous-wave Doppler sonography [13, 21]and Duplex scanning [10, 11, 12, 14, 15, 18, 19]without color Doppler. Only 5 recent papers have used color-coded Doppler for examination of the vertebral arteries [16, 17, 20, 22, 23]. A previous study [22]reported color-coded Doppler of the vertebral artery in 85 normal individuals and in 166 patients with atheromatous diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concerning the quantification of proximal VA stenosis by ultrasound are not recent and are limited in number [10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23]. They used continuous-wave Doppler sonography [13, 21]and Duplex scanning [10, 11, 12, 14, 15, 18, 19]without color Doppler.…”
Section: Discussionmentioning
confidence: 99%